Defining new communities: a challenge for immigrant health - DECENA, Carlos Ulises; SHEDLIN, Michele (Papeles de Población, 2005)
Efforts to reduce HIV/AIDS vulnerability among U.S. Hispanics/Latinos can benefit from conceptualizing immigrant populations in ways that reflect their composition, social dynamics, economic and health status and permanency. This study employed qualitative methods to identify and describe HIV/AIDS and other health vulnerabilities among recent immigrants to the New York area from Guatemala, El Salvador, Honduras, the Dominican Republic and Mexico. Qualitative data collection involved: a) individual interviews (n = 51); b) 11 focusing groups (n = 86); c) key informant interviews (n = 26) and one focusing group with advocates and providers in health and social services; and d) ethnographic observation. Results indicate that migration and living conditions in receiving locations contribute to new immigrants’ disconnection from a sense of “community” that may have negative effects on their physical and mental health. Data support the conclusion that public health policies and programs need to reach some consensus in defining these evolving immigrant “communities” in order to determine and provide culturally appropriate and effective prevention interventions.